Double-layer wave absorbing structure and preparation method thereof

By designing a double-layer wave absorbing structure, the combination of polylactic acid matrix and different fillers can achieve a gradual change in the electromagnetic wave impedance of the surface and interface, solving the problems of narrow frequency bands of the existing wave absorbing coating and low interface strength of the material, and achieving the high-performance stealth and wide-band electromagnetic loss performance of the aircraft.

CN119730222AActive Publication Date: 2025-03-28CHINA ACAD OF AEROSPACE AERODYNAMICS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411963084.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The frequency bands of existing wave absorbing coatings are narrow, the material interface strength is low, making it difficult to achieve wide-band stealth, and a single component wave absorbing coating is difficult to achieve high electromagnetic loss performance.

Method used

A double-layer absorbing structure is designed, with the loss dielectric layer A as the surface layer, the base material is polylactic acid, and the filler is spherical carbonyl iron; the loss dielectric layer B as the bottom layer, the base material is polylactic acid, and the filler is nanocarbon particles. Prepared through the melt deposition molding process, appropriate gradation of the electromagnetic wave impedance of the surface and interface is achieved, and the electromagnetic loss performance is improved.

Benefits of technology

The high-performance stealth of the aircraft is achieved, and the effective absorption bandwidth of the double-layer wave absorbing structure is significantly better than that of the existing technology and has stronger electromagnetic loss performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730222A_ABST
    Figure CN119730222A_ABST
Patent Text Reader

Abstract

The invention provides a double-layer wave-absorbing structure and a preparation method thereof. The double-layer wave-absorbing structure comprises a loss dielectric layer A and a loss dielectric layer B, the loss dielectric layer A is used as a surface layer, a base material is polylactic acid, and a filler is spherical carbonyl iron; the loss dielectric layer B is used as a bottom layer, the base material is polylactic acid, and the filler is nano carbon particles. And curing the loss dielectric layer A and the loss dielectric layer B through a fused deposition modeling 3D printing process to obtain the double-layer wave-absorbing structure. The loss dielectric layer A serves as a surface layer, surface wave impedance is larger than interface wave impedance, the impedance matching degree is good, surface input impedance and free space wave impedance matching are utilized, front reflection of electromagnetic waves at the interface of air and the absorber is reduced, most of the electromagnetic waves enter the material, and the absorption efficiency is improved. And then the high dielectric loss and magnetic loss material absorbs the energy of the electromagnetic wave.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wave absorbing materials, and in particular relates to a double-layer wave absorbing structure and a preparation method thereof. Background Art

[0002] Absorbing materials are an important means to achieve stealth technology. The existing absorbing coatings are applicable to a narrow frequency band, mainly covering the 8-12 GHz frequency band, and the interface strength of the coating material is low. It is difficult for a single-component absorbing coating to meet the requirements of broadband stealth. Therefore, a stacking design of multiple absorbing materials is required to achieve a gradual change in the electromagnetic wave impedance inside the material, that is, from the surface material to the reflective backing, the wave impedance decreases successively. By matching the surface input impedance with the wave impedance of free space, the frontal reflection of electromagnetic waves at the interface between air and materials is reduced, so that most of the electromagnetic waves enter the interior of the material, and then the energy of the electromagnetic waves is absorbed by the high dielectric loss and magnetic loss materials. Summary of the invention

[0003] In order to overcome the deficiencies in the prior art, the inventors have conducted intensive research and provided a double-layer absorbing structure and a preparation method thereof. The surface and interface electromagnetic wave impedance of the structure are appropriately gradually changed to improve the electromagnetic loss performance and achieve high-performance stealth of the aircraft.

[0004] The technical solution provided by the present invention is as follows: In a first aspect, a double-layer absorbing structure includes a lossy dielectric layer A and a lossy dielectric layer B; The lossy dielectric layer A is used as the surface layer, the base material is polylactic acid, and the filler is spherical carbonyl iron; The lossy dielectric layer B is used as the bottom layer, the matrix material is polylactic acid, and the filler is nano-carbon particles.

[0005] In combination with the first aspect, the mass fraction of carbonyl iron in the lossy dielectric layer A is 40% to 70%, and the mass fraction of polylactic acid is 30% to 60%.

[0006] In combination with the first aspect, the mass fraction of the nano-carbon particles in the lossy dielectric layer B is 10% to 30%, and the mass fraction of the polylactic acid is 70% to 90%.

[0007] In combination with the first aspect, the thickness of the double-layer absorbing structure is 3-5 mm, the thickness of the lossy dielectric layer A is 1-4 mm, and the thickness of the lossy dielectric layer B is 1-4 mm. Preferably, the thickness of the lossy dielectric layer A is less than the thickness of the lossy dielectric layer B.

[0008] In a second aspect, a method for preparing a double-layer absorbing structure comprises the following steps: Carbonyl iron and polylactic acid are used to prepare carbonyl iron polylactic acid composite wire; Nanocarbon particles and polylactic acid are used to prepare nanocarbon particle polylactic acid composite wires; A lossy dielectric layer B is formed by a fused deposition molding process using nano-carbon particle polylactic acid composite wire; on the lossy dielectric layer B, a lossy dielectric layer A is formed by a fused deposition molding process using a carbonyl iron polylactic acid composite wire to obtain a double-layer absorbing structure.

[0009] A double-layer absorbing structure and a preparation method thereof provided by the present invention have the following beneficial effects: (1) The present invention provides a double-layer absorbing structure and a preparation method thereof, wherein the lossy dielectric layer A of the double-layer absorbing structure is used as the surface layer, the matrix material is polylactic acid, and the filler is spherical carbonyl iron; the lossy dielectric layer B is used as the bottom layer, the matrix material is polylactic acid, and the filler is nano-carbon particles. The lossy dielectric layer A is used as the surface layer, the surface wave impedance is greater than the interface wave impedance, and the impedance matching is good. The surface input impedance and the wave impedance of the free space are matched to reduce the front reflection of the electromagnetic wave at the interface between the air and the absorber, so that most of the electromagnetic wave enters the interior of the material, and then the energy of the electromagnetic wave is absorbed by the high dielectric loss and magnetic loss material; (2) The present invention provides a double-layer absorbing structure and a preparation method thereof. The composite wire used in the molten deposition molding process is obtained by a two-step melt blending preparation process, so that the mass ratio and dispersibility of the absorber are significantly improved, thereby realizing the preparation of absorbing composite wires with high electromagnetic loss performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 It is a schematic diagram of a double-layer absorbing structure; Figure 2 The wave absorption performance analysis of the double-layer structure of the surface layer 1mm (CI-60 / PLA) and the bottom layer 4mm (NPC-20 / PLA) in Example 1; Figure 3 The wave absorption performance analysis of the double-layer structure of the surface layer 1mm (NPC-20 / PLA) and the bottom layer 4mm (CI-60 / PLA) of comparative example 1; Figure 4 The wave absorption performance analysis of the double-layer structure of the surface layer 2mm (CI-60 / PLA) and the bottom layer 3mm (NPC-20 / PLA) in Example 2; Figure 5 The wave absorption performance analysis of the double-layer structure of the surface layer 2mm (NPC-20 / PLA) and the bottom layer 3mm (CI-60 / PLA) of comparative example 2; Figure 6 The wave absorption performance analysis of the double-layer structure of the surface layer 3mm (CI-60 / PLA) and the bottom layer 2mm (NPC-20 / PLA) of Example 3; Figure 7The wave absorption performance analysis of the double-layer structure of the surface layer 3mm (NPC-20 / PLA) and the bottom layer 2mm (CI-60 / PLA) of comparative example 3; Figure 8 The wave absorption performance analysis of the double-layer structure of the surface layer 4 mm (CI-60 / PLA) and the bottom layer 1 mm (NPC-20 / PLA) of Example 4; Fig. 9 The wave absorption performance analysis of the double-layer structure of the surface layer 4mm (NPC-20 / PLA) and the bottom layer 1mm (CI-60 / PLA) of comparative example 4; Fig.10 The microwave absorbing performance of the double-layer structure of Examples 1 to 4 is summarized and analyzed. DETAILED DESCRIPTION

[0011] The following detailed description of the present invention will make the features and advantages of the present invention more clear and explicit.

[0012] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.

[0013] The present invention provides a double-layer wave absorbing structure, such as Figure 1 As shown, it includes a lossy dielectric layer A and a lossy dielectric layer B; The lossy dielectric layer A is used as the surface layer, the base material is polylactic acid (PLA), and the filler is spherical carbonyl iron (CI); The lossy dielectric layer B is used as the bottom layer, the matrix material is polylactic acid, and the filler is nanocarbon particles (NPC); The lossy dielectric layer A and the lossy dielectric layer B are solidified and combined through a fused deposition modeling process to obtain a double-layer absorbing structure.

[0014] The mass fraction of carbonyl iron in the lossy dielectric layer A is 40%~70%, and the mass fraction of polylactic acid is 30%~60%; preferably, the mass fraction of carbonyl iron in the lossy dielectric layer A is 40%~60%, and the mass fraction of polylactic acid is 40%~60%; more preferably, the mass fraction of carbonyl iron in the lossy dielectric layer A is 55%~60%, and the mass fraction of polylactic acid is 40%~45%.

[0015] The mass fraction of the nano-carbon particles in the lossy dielectric layer B is 10%~30%, and the mass fraction of the polylactic acid is 70%~90%; preferably, the mass fraction of the nano-carbon particles in the lossy dielectric layer B is 10%~20%, and the mass fraction of the polylactic acid is 80%~90%; more preferably, the mass fraction of the nano-carbon particles in the lossy dielectric layer B is 15%~20%, and the mass fraction of the polylactic acid is 85%~90%.

[0016] The thickness of the double-layer absorbing structure is 3-5 mm, the thickness of the lossy dielectric layer A is 1-4 mm, and the thickness of the lossy dielectric layer B is 1-4 mm; preferably, the thickness of the lossy dielectric layer A is 1-2 mm, and the thickness of the lossy dielectric layer B is 2-4 mm. More preferably, the thickness of the lossy dielectric layer A is less than the thickness of the lossy dielectric layer B.

[0017] The working principle of the double-layer absorbing structure: The wave impedance decreases from the surface of the lossy dielectric layer A to the interface between the lossy dielectric layers A and B. The surface input impedance and the wave impedance of the free space are matched to reduce the front reflection of the electromagnetic wave at the interface between the air and the absorber, so that most of the electromagnetic wave enters the material, and then the energy of the electromagnetic wave is absorbed by the high dielectric loss material (lossy dielectric layer B) and the magnetic loss material (lossy dielectric layer A).

[0018] The present invention also provides a method for preparing a double-layer wave absorbing structure, comprising the following steps: (1) Using carbonyl iron and polylactic acid to prepare a carbonyl iron polylactic acid composite material comprises the following steps: S1, drying carbonyl iron and polylactic acid powder in an oven at 80-100°C for at least 12 h; S2, dispersing the proportional mixture of carbonyl iron and polylactic acid in a planetary mixer at a speed of 60-100 r / min for at least 8 h; S3, melting and mixing the mixture and extruding it through a pelletizer to form composite pellets; S4, pour the dried composite material particles into a single screw extruder, the composite particles are heated and melted in the screw, and further mixed under the action of screw friction and shear. The molten mixture is extruded from the die, and the composite wire is obtained by the dual action of water tank cooling and traction sizing, such as a 1.75 diameter 0.05 mm composite wire.

[0019] (2) Using nano-carbon particles and polylactic acid to prepare a nano-carbon particle polylactic acid composite material comprises the following steps: S1, drying the nanocarbon particles and polylactic acid powder in an oven at 80-100 °C for at least 12 h; S2, dispersing the proportion of nanocarbon particles and polylactic acid in a planetary mixer at a speed of 60-100 r / min for at least 8 h; S3, melting and mixing the mixture and extruding it through a pelletizer to form composite pellets; S4, pour the dried composite material particles into a single screw extruder, the composite particles are heated and melted in the screw, and further mixed under the action of screw friction and shear. The molten mixture is extruded from the die, and the composite wire is obtained by the dual action of water tank cooling and traction sizing, such as a 1.75 diameter 0.05 mm composite wire.

[0020] (3) Using nano-carbon particle polylactic acid composite wire, the lossy dielectric layer B is formed by the fused deposition molding process; on the lossy dielectric layer B, the carbonyl iron polylactic acid composite wire is used to form the lossy dielectric layer A by the fused deposition molding process to obtain a double-layer absorbing structure. The optimal printing temperature of the composite wire is 200~230℃, and the printing speed is 30~40 mm / s.

[0021] The effective absorbing bandwidth (reflection loss less than -10 dB) of the lossy dielectric layer A and lossy dielectric layer B prepared by the present invention at a matching thickness of 3 mm is significantly better than that of the absorbing composite wire in the literature, and has stronger electromagnetic loss performance. This is due to the two-step melt blending preparation process, which significantly improves the mass ratio and dispersibility of the absorbent, and realizes the preparation of the absorbing composite wire with high electromagnetic loss performance.

[0022] Table 1 Comparison of the performance of the microwave absorbing composite wires reported in the literature and prepared by the present invention

[0023] Note: CI-60 / PLA means that the mass content of carbonyl iron is 60%, and the rest is the matrix material PLA; NPC-20 / PLA means that the mass content of nanocarbon particles is 20%, and the rest is the matrix material PLA.

[0024] [1] Hu Zhenglang, Wu Haihua, Yang Zenghui, et al. Preparation and microwave absorption properties of graphene-iron-nickel alloy-polylactic acid composites. Journal of Composite Materials, 2022, 39: 1-14.

[0025] [2] Ye Xicong, Yang Chao, Ouyang Bin, et al. Graphene enhanced FeSiAl-MoS 2 / PLA composites absorbent properties. Journal of Composite Materials, 2023, 40(2): 911-928.

[0026] [3]Duan Y, Liang Q, Yang Z, et al. A wide-angle broadband electromagnetic absorbing metastructure using 3D printing technology. Materials&Design, 2021, 208: 109900. [4] Ye Xicong, Ouyang Bin, Yang Chao, et al. Preparation of graphene-carbonyl iron powder wire and analysis of its microwave absorption performance. Journal of Composite Materials, 2021, 39: 1-12.

[0027] Example Example 1 and Comparative Example 1 Embodiment 1 provides a method for preparing a double-layer absorbing structure, which comprises the following steps: (1) Using carbonyl iron and polylactic acid to prepare a carbonyl iron polylactic acid composite material comprises the following steps: S1, drying carbonyl iron and polylactic acid powder in an oven at 80 °C for 12 h; S2, a mixture of carbonyl iron and polylactic acid with a mass ratio of 6:4 was dispersed in a planetary mixer at a speed of 60 r / min for 8 h; S3, melting and mixing the mixture and extruding it through a pelletizer to form composite pellets; S4, pour the dried composite material particles into the single screw extruder, the composite particles are heated and melted in the screw, and further mixed under the action of screw friction and shear. The molten mixture is extruded from the die, and the diameter of 1.75 mm is obtained under the dual action of water tank cooling and traction sizing. 0.05 mm composite wire CI-60 / PLA.

[0028] (2) Using nano-carbon particles and polylactic acid to prepare a nano-carbon particle polylactic acid composite material comprises the following steps: S1, drying the nanocarbon particles and polylactic acid powder in an oven at 80 °C for 12 h; S2, a mixture of nanocarbon particles and polylactic acid with a mass ratio of 2:8 was dispersed in a planetary mixer at a speed of 60 r / min for 8 h; S3, melting and mixing the mixture and extruding it through a pelletizer to form composite pellets; S4, pour the dried composite material particles into the single screw extruder, the composite particles are heated and melted in the screw, and further mixed under the action of screw friction and shear. The molten mixture is extruded from the die, and the diameter of 1.75 mm is obtained under the dual action of water tank cooling and traction sizing. 0.05 mm composite wire NPC-20 / PLA.

[0029] (3) Using nano-carbon particle polylactic acid absorbing composite wire, the lossy dielectric layer B is formed by the fused deposition molding process; on the lossy dielectric layer B, the carbonyl iron polylactic acid absorbing composite wire is used to form the lossy dielectric layer A by the fused deposition molding process to obtain a double-layer absorbing structure CI-60-1mm / NPC-20-4mm. The printing temperature of the wire is 230℃ and the printing speed is 40 mm / s.

[0030] The double-layer absorbing structure CI-60-1mm / NPC-20-4mm has lossy dielectric layer A (CI-60 / PLA) as the surface layer with a thickness of 1mm; and lossy dielectric layer B (NPC-20 / PLA) as the bottom layer with a thickness of 4mm; the total thickness of the double-layer absorbing structure is 5mm.

[0031] As comparative example 1, a double-layer absorbing structure NPC-20-1mm / CI-60-4mm was prepared, with lossy dielectric layer B (NPC-20 / PLA) as the surface layer with a thickness of 1mm; and lossy dielectric layer A (CI-60 / PLA) as the bottom layer with a thickness of 4mm, and a total thickness of 5mm.

[0032] Example 1 uses CI-60 / PLA as the surface layer (thickness 1 mm) of the double-layer absorbing material, and uses NPC-20 / PLA as the bottom layer (thickness 4 mm) of the double-layer absorbing material. The curves of the surface reflection loss and interface wave impedance of the double-layer structure changing with frequency are shown in Figure 2 As shown in the figure, there are two absorption peaks in the frequency range, and the corresponding reflection loss values ​​are -36.9 dB (4.8 GHz) and -23.2 dB (16.7 GHz), respectively. The effective absorption bands are 3.8-6.4 GHz and 14.9-18 GHz, respectively. The reflection loss values ​​in the 6.4-14.9 GHz band are all less than -5.8 dB, which has a certain electromagnetic loss capacity and is evenly distributed. From the wave impedance mode, it can be seen that in the 2.6-5.5 GHz and 10.4-18 GHz bands, the surface wave impedance is greater than the interface wave impedance, which conforms to the gradual change of wave impedance. Therefore, the effective absorption bands where the two absorption peaks are located are within the range of these two frequency bands.

[0033] Comparative Example 1 uses NPC-20 / PLA as the surface layer (thickness 1 mm) of the double-layer absorbing material, and uses CI-60 / PLA as the bottom layer (thickness 4 mm) of the double-layer absorbing material. The curves of the surface reflection loss and interface wave impedance of the double-layer structure with frequency are shown in Figure 1. Figure 3 As shown in the figure, the effective reflection loss frequency band is 3.4-5.2 GHz, and the minimum reflection loss is -24.8 dB (4.2GHz). The electromagnetic loss performance of the structure is not as good as the solution using CI-60 / PLA as the surface layer. From the wave impedance model, it can be seen that in the 4.5-15.2 GHz frequency band, the surface wave impedance is smaller than the interface wave impedance, and the electromagnetic wave impedance mismatch causes the electromagnetic wave to be reflected.

[0034] Example 2 and Comparative Example 2 Example 2: A double-layer absorbing structure CI-60-2mm / NPC-20-3mm is formed by the preparation method in Example 1. The double-layer absorbing structure CI-60-2mm / NPC-20-3mm has a lossy dielectric layer A (CI-60 / PLA) as a surface layer with a thickness of 2mm; and a lossy dielectric layer B (NPC-20 / PLA) as a bottom layer with a thickness of 3mm. The total thickness is 5mm.

[0035] In Comparative Example 2, the preparation method in Example 1 was used to form a double-layer absorbing structure NPC-20-2mm / CI-60-3mm. The double-layer absorbing structure NPC-20-2mm / CI-60-3mm had a lossy dielectric layer A (CI-60 / PLA) as the surface layer with a thickness of 2mm, and a lossy dielectric layer B (NPC-20 / PLA) as the bottom layer with a thickness of 3mm. The total thickness was 5mm.

[0036] Example 2 uses CI-60 / PLA as the surface layer (thickness 2 mm) of the double-layer absorbing material, and uses NPC-20 / PLA as the bottom layer (thickness 3 mm) of the double-layer absorbing material. The curves of the surface reflection loss and interface wave impedance of the double-layer structure with frequency are shown in Figure 2. Figure 4 As shown in the figure, there are two absorption peaks in the frequency range, and the corresponding reflection loss values ​​are -13.8 dB (5.7 GHz) and -16.3 dB (15.8 GHz), respectively. The effective absorption bands are 4.8-7.2 GHz and 13.6-18 GHz, respectively. The reflection loss values ​​in the 7.2-13.6 GHz band are all less than -7.1 dB, which has a certain electromagnetic loss capacity and is relatively evenly distributed. From the wave impedance mode, it can be seen that in the 2.6-7.2 GHz and 12.6-18 GHz bands, the surface wave impedance is greater than the interface wave impedance, which conforms to the gradual change of wave impedance. Therefore, the effective absorption bands where the two absorption peaks are located are within the range of these two frequency bands.

[0037] Comparative Example 2 uses NPC-20 / PLA as the surface layer (thickness 2 mm) of the double-layer absorbing material, and uses CI-60 / PLA as the bottom layer (thickness 3 mm) of the double-layer absorbing material. The curves of the surface reflection loss and interface wave impedance of the double-layer structure with frequency are shown in Figure 2. Figure 5 As shown in the figure, the effective reflection loss frequency band is 3.0-4.7 GHz, and the minimum reflection loss is -20.0 dB (3.8 GHz). The electromagnetic loss performance of the structure is not as good as that of the solution using CI-60 / PLA as the surface layer. From the wave impedance model, it can be seen that in the 4.6-15.9 GHz frequency band, the surface wave impedance is smaller than the interface wave impedance, and the electromagnetic wave impedance mismatch causes the electromagnetic wave to be reflected.

[0038] Example 3 and Comparative Example 3 Example 3 The preparation method in Example 1 is used to form a double-layer absorbing structure CI-60-3mm / NPC-20-2mm. The double-layer absorbing structure CI-60-3mm / NPC-20-2mm has a lossy dielectric layer A (CI-60 / PLA) as a surface layer with a thickness of 3mm; and a lossy dielectric layer B (NPC-20 / PLA) as a bottom layer with a thickness of 2mm. The total thickness is 5mm.

[0039] In Comparative Example 3, the preparation method in Example 1 was used to form a double-layer absorbing structure NPC-20-3mm / CI-60-2mm. The double-layer absorbing structure NPC-20-3mm / CI-60-2mm had a lossy dielectric layer A (CI-60 / PLA) as a surface layer with a thickness of 3mm, and a lossy dielectric layer B (NPC-20 / PLA) as a bottom layer with a thickness of 2mm. The total thickness was 5mm.

[0040] Example 3 uses CI-60 / PLA as the surface layer (thickness 3 mm) of the double-layer absorbing material, and uses NPC-20 / PLA as the bottom layer (thickness 2 mm) of the double-layer absorbing material. The curves of the surface reflection loss and interface wave impedance of the double-layer structure changing with frequency are shown in Figure 6 As shown in the figure, two absorption peaks appear in the frequency range, and the corresponding reflection loss values ​​are -7.8 dB (5.8 GHz) and -12.0 dB (16.5 GHz), respectively. The effective absorption frequency band is 15.3-18.0 GHz. Since the frequency band near the first absorption peak does not achieve effective absorption, the effective absorption frequency band is relatively reduced. From the wave impedance model, it can be seen that in the 2.6-9.3 GHz and 16.8-18.0 GHz frequency bands, the surface wave impedance is greater than the interface wave impedance, the impedance matching is better, and two absorption peaks will appear. The high reflection loss value corresponding to the first absorption peak is related to the attenuation characteristics of the constituent materials.

[0041] Comparative Example 3 uses NPC-20 / PLA as the surface layer (thickness 3 mm) of the double-layer absorbing material, and uses CI-60 / PLA as the bottom layer (thickness 2 mm) of the double-layer absorbing material. The curves of the surface reflection loss and interface wave impedance of the double-layer structure with frequency are shown in Figure 2. Figure 7 As shown in the figure, the effective reflection loss frequency bands are 3.0-4.5 GHz and 16.2-18 GHz, and the minimum reflection loss is -15.2dB (3.6 GHz). The electromagnetic loss performance of the structure is not as good as that of the solution using CI-60 / PLA as the surface layer. From the wave impedance model, it can be seen that in the 5.4-18.0 GHz frequency band, the surface wave impedance is smaller than the interface wave impedance, and the mismatch of electromagnetic wave impedance leads to a large amount of electromagnetic waves being reflected.

[0042] Example 4 and Comparative Example 4 Example 4 The preparation method in Example 1 is used to form a double-layer absorbing structure CI-60-4mm / NPC-20-1mm. The double-layer absorbing structure CI-60-4mm / NPC-20-1mm has a lossy dielectric layer A (CI-60 / PLA) as a surface layer with a thickness of 4mm; and a lossy dielectric layer B (NPC-20 / PLA) as a bottom layer with a thickness of 1mm, and a total thickness of 5mm.

[0043] In Comparative Example 4, the preparation method in Example 1 was used to form a double-layer absorbing structure NPC-20-4mm / CI-60-1mm. The double-layer absorbing structure NPC-20-4mm / CI-60-1mm had a lossy dielectric layer A (CI-60 / PLA) as a surface layer with a thickness of 4mm; and a lossy dielectric layer B (NPC-20 / PLA) as a bottom layer with a thickness of 1mm. The total thickness was 5mm.

[0044] Example 4 uses CI-60 / PLA as the surface layer (thickness 4 mm) of the double-layer absorbing material, and uses NPC-20 / PLA as the bottom layer (thickness 1 mm) of the double-layer absorbing material. The curves of the surface reflection loss and interface wave impedance of the double-layer structure changing with frequency are shown in Figure 8 As shown in the figure, two absorption peaks appear in the frequency range, and the corresponding reflection loss values ​​are -7.5 dB (5.6 GHz) and -17.7 dB (17.5 GHz), respectively, and the effective absorption frequency band is 15.9-18.0 GHz. Since the frequency band near the first absorption peak does not achieve effective absorption, the effective absorption frequency band is relatively reduced. From the wave impedance model, it can be seen that in the 2.6-12.4 GHz and 14.4-18.0 GHz frequency bands, the surface wave impedance is greater than the interface wave impedance, the impedance matching is better, and two absorption peaks will appear. The high reflection loss value corresponding to the first absorption peak is related to the attenuation characteristics of the constituent materials.

[0045] Comparative Example 4 uses NPC-20 / PLA as the surface layer (thickness 4 mm) of the double-layer absorbing material, and uses CI-60 / PLA as the bottom layer (thickness 1 mm) of the double-layer absorbing material. The curves of the surface reflection loss and interface wave impedance of the double-layer structure with frequency are shown in Figure 2. Fig. 9 As shown in the figure, the effective reflection loss frequency band is 3.1-4.5 GHz, and the minimum reflection loss is -14.7 dB (3.6 GHz). The electromagnetic loss performance of the structure is not as good as that of the solution using CI-60 / PLA as the surface layer. From the wave impedance model, it can be seen that in the 7.3-18.0 GHz frequency band, the surface wave impedance is smaller than the interface wave impedance, and the electromagnetic wave impedance mismatch causes a large amount of electromagnetic waves to be reflected.

[0046] In summary, CI-60 / PLA and NPC-20 / PLA composite materials were selected to design a double-layer structure, and the total thickness of the double-layer structure was constrained to be 5 mm. CI-60 / PLA was used as the surface layer of the double-layer absorbing material (thickness ranged from 1 to 4 mm), and NPC-20 / PLA was used as the bottom layer of the double-layer absorbing material (thickness ranged from 4 to 1 mm). The surface reflection loss curves of the four designed double-layer structures as a function of frequency are shown in Figure 2. Fig.10 As shown in the figure, it can be seen that as the thickness of the surface layer decreases, the positions of the two absorption peak frequencies move to both sides, and the effective absorption bandwidth expands. Among them, the double-layer structure of CI-60 / PLA with a surface layer of 1 mm and NPC-20 / PLA with a bottom layer of 4 mm has the best electromagnetic loss capacity, and the effective absorption frequency band is 3.8~6.4 GHz and 14.9~18 GHz. The reflection loss values ​​in the 6.4~14.9 GHz frequency band are all less than -5.8 dB, which has a certain electromagnetic loss capacity and is relatively evenly distributed.

[0047] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

[0048] The contents not described in detail in the specification of the present invention belong to the common knowledge of those skilled in the art.

Claims

1. A double-layer absorbing structure, characterized in that: including a lossy dielectric layer A and a lossy dielectric layer B; The lossy dielectric layer A is used as the surface layer, the base material is polylactic acid, and the filler is spherical carbonyl iron; The lossy dielectric layer B is used as the bottom layer, the matrix material is polylactic acid, and the filler is nano-carbon particles.

2. The double-layer absorbing structure according to claim 1, characterized in that: The mass fraction of carbonyl iron in the lossy dielectric layer A is 40% to 70%, and the mass fraction of polylactic acid is 30% to 60%.

3. The double-layer absorbing structure according to claim 1, characterized in that: The mass fraction of the nano-carbon particles in the lossy dielectric layer B is 10% to 30%, and the mass fraction of the polylactic acid is 70% to 90%.

4. The double-layer absorbing structure according to claim 1, characterized in that: The thickness of the double-layer absorbing structure is 3-5 mm, the thickness of the lossy dielectric layer A is 1-4 mm, and the thickness of the lossy dielectric layer B is 1-4 mm.

5. The double-layer absorbing structure according to claim 1, characterized in that: The thickness of the lossy dielectric layer A is smaller than the thickness of the lossy dielectric layer B.

6. A method for preparing a double-layer absorbing structure according to any one of claims 1 to 5, characterized in that: The steps include: Carbonyl iron and polylactic acid are used to prepare carbonyl iron polylactic acid composite wire; Nanocarbon particles and polylactic acid are used to prepare nanocarbon particle polylactic acid composite wires; A lossy dielectric layer B is prepared by a fused deposition modeling process using nano-carbon particle polylactic acid composite wire; on the lossy dielectric layer B, a lossy dielectric layer A is prepared by a fused deposition modeling process using carbonyl iron polylactic acid composite wire to obtain a double-layer absorbing structure.

7. The method for preparing a double-layer absorbing structure according to claim 6, characterized in that: The step of preparing the carbonyl iron-polylactic acid composite wire by using carbonyl iron and polylactic acid comprises: drying carbonyl iron and polylactic acid powder; The proportioned mixture of carbonyl iron and polylactic acid is fully dispersed in a planetary mixer; The mixture is melted, mixed and extruded through a pelletizer to form composite pellets; The dried composite material particles are poured into a screw extruder, and the molten mixture is extruded from a die, and composite wires are obtained through the dual effects of cooling and traction sizing.

8. The method for preparing a double-layer absorbing structure according to claim 6, characterized in that: The step of using nano-carbon particles and polylactic acid to prepare a nano-carbon particle polylactic acid composite wire comprises: drying the nanocarbon particles and the polylactic acid powder; The proportioned mixture of nanocarbon particles and polylactic acid is fully dispersed in a planetary mixer; The mixture is melted, mixed and extruded through a pelletizer to form composite pellets; The dried composite material particles are poured into a screw extruder, and the molten mixture is extruded from a die, and composite wires are obtained through the dual effects of cooling and traction sizing.

9. The method for preparing a double-layer absorbing structure according to claim 6, characterized in that: When the lossy dielectric layer A and the lossy dielectric layer B are formed by the fused deposition modeling process, the printing temperature of the composite wire is 200~230℃ and the printing speed is 30~40 mm / s.

Citation Information

Patent Citations

  • Preparation method of structural broadband wave-absorbing material based on 3D printing technology

    CN110690579A

  • Wide-angle wave absorbing structure design method based on additive manufacturing

    CN111695217A

  • Ultra-wideband wave-absorbing material and preparation method thereof

    CN113161761A